Notes on a synonymy in the tribe Platyscelidini (Coleoptera: Tenebrionidae) - M.V. Nabozhenko (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
Reitter described two genus-rank taxa within the tenebrionid tribe Helopini (Tenebrionidae) in the same work: Euryhelops Reitter, 1902 (type species Helops tiro Reitter, 1902) as a subgenus of the genus Helops Fabricius, 1775 and Euryhelops Reitter, 1902 as a separate genus (type species Helops championi Reitter, 1891 = Helops subaeneus Reitter, 1889). He eliminated this homonymy in the same 1902 but in a different paper and proposed the generic name Zophohelops Reitter, 1902 (Helopini) for the first taxon. The second taxon Euryhelops was erroneously placed as a junior synonym to the subgenus Cardiobioramix Kaszab, 1940 (type species Bioramix asidioides Bates, 1879) in the genus Bioramix Bates, 1879 (Platyscelidini). Both type species of Euryhelops and Cardiobioramix are consubgeneric, therefore we reinstate the priority of the name Euryhelops as a subgenus within the genus Bioramix and propose the following synonymy: Euryhelops Reitter, 1902, subgen. resurr. = = Cardiobioramix Kaszab, 1940, syn. n.